The Infiltration-centrifugation Technique for Extraction of Apoplastic Fluid from Plant Leaves Using Phaseolus vulgaris as an Example - O'Leary, Brendan M. (J Vis Exp, 2014)
The apoplast is a distinct extracellular compartment in plant tissues that lies outside the plasma membrane and includes the cell wall. The apoplastic compartment of plant leaves is the site of several important biological processes, including cell wall formation, cellular nutrient and water uptake and export, plant-endophyte interactions and defence responses to pathogens. The infiltration-centrifugation method is well established as a robust technique for the analysis of the soluble apoplast composition of various plant species. The fluid obtained by this method is commonly known as apoplast washing fluid (AWF). The following protocol describes an optimized vacuum infiltration and centrifugation method for AWF extraction from Phaseolus vulgaris (French bean) cv. Tendergreen leaves. The limitations of this method and the optimization of the protocol for other plant species are discussed. Recovered AWF can be used in a wide range of downstream experiments that seek to characterize the composition of the apoplast and how it varies in response to plant species and genotype, plant development and environmental conditions, or to determine how microorganisms grow in apoplast fluid and respond to changes in its composition.